加工螺旋面的成形盘铣刀刃磨原理及应用 - 方成刚; 巩建鸣; 郭二廓; 张虎; 黄筱调 (Jixie chuandong)
Aiming at the problem of the regrinding forming disk milling cutter blade surface is complex,it is difficult to machine by using 3-axis CNC machine tools.To calculate the complex profile of forming disk milling cutter,the mathematical model of grinding forming disk milling cutter is established according to the space coordinate transformation.A method to obtain the tool path for grinding free-form surface by using 3-axis CNC machine tools is proposed.By matching the vector of cutter profile to the vector of contact point on grind wheel,then matching the coordinate points in the cutter profile to the contact points on grind wheel,consequently,the tool path is obtained.The error of enveloped profile along the tool path is less than 0.6μm and can meet the requirements of grinding.Grinding and milling results show that the method for grinding free-form profile is valid by using the 3-axis CNC machine.